2019
DOI: 10.13005/bpj/1778
|View full text |Cite
|
Sign up to set email alerts
|

An Innovative Effective Nutritional Therapy for Vitamin D Deficiency in Children with Celiac Disease

Abstract: Children with celiac disease (CD) are susceptible to reduced bone mineral density (BMD). Our target is to assess the severity of vitamin D deficiency in CD children on a gluten-free diet (GFD), and to evaluate the effectiveness of adding an innovative GF meal, on the clinical and bone biochemical indices of CD patients. 50 CD children who were diagnosed and followed up at Pediatric gastroenterology clinic, Specialized pediatric hospital, Cairo University; by serology and biopsy of the duodenum were included in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…Vitamin D is a steroid hormone that has a great role in calcium and phosphorus homeostasis, bone metabolism and bone development [5], [6]. Recently the role of vitamin D on glucose homeostasis, cardiovascular diseases, immune system and cancer has been reported [7], [8].…”
Section: Introductionmentioning
confidence: 99%
“…Vitamin D is a steroid hormone that has a great role in calcium and phosphorus homeostasis, bone metabolism and bone development [5], [6]. Recently the role of vitamin D on glucose homeostasis, cardiovascular diseases, immune system and cancer has been reported [7], [8].…”
Section: Introductionmentioning
confidence: 99%
“…The level of serum zinc and iron in our research displayed significant increase in the controls in comparison to the cases (p < 0.001). The previous researches revealed that serum zinc showed a significant difference between non-malnourished children and other children affected with mild to severe growth deficits [19], [20]. Bains et al [21] recorded that iron and zinc were significantly lower in children <5 years living in poor and rural families who suffer from malnutrition.…”
Section: Discussionmentioning
confidence: 99%
“…Vitamin D is involved in the processes of bone mineralization and growth through the regulation of calcium and phosphorus homeostasis [39]. The main site of Vitamins A and D absorption is small intestine which is the place of EED pathology [40].…”
Section: Discussionmentioning
confidence: 99%